Prototype of a Multisensor Fire Detection System Based on the Internet of Things (IoT) - Rofiq, Mohamad; Aribowo, Didik; Desmira, Desmira (Jurnal Inovasi Pendidikan dan Sains, 2025)
Fire is a disaster that cannot be predicted and often has a significant impact on human life, both materially and non-materially. Fires are usually detected only after they have grown large, resulting in unavoidable losses. Various factors, such as short circuits in electrical networks, LPG gas leaks, and human negligence, are the main causes of fires. In this situation, an early detection system that provides real-time information is needed to minimize the impact of the fire. This study aims to design a prototype of a Multisensor Fire Detection System Based on the Internet of Things (IoT) that integrates a flame sensor, MQ-2 gas sensor, and DHT22 temperature sensor with the Blynk application to provide real-time notifications. This system is also equipped with an LCD for warning display and a buzzer as an alarm. The prototype has been tested in a controlled environment that simulates fire conditions, including gas leaks and high temperatures, with several trials conducted to verify its reliability. The results showed that the system could detect fire at a maximum distance of 100 cm, hazardous gas concentrations starting from 600 ppm, and temperatures exceeding 35°C as the threshold for fire detection. However, its performance may be affected in environments with high humidity levels or areas with poor network connectivity. With effective integration of hardware and software, this prototype helps users detect potential fires at an early stage and minimize the risk of fire-related losses